2014
DOI: 10.3791/50712
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Efficient Method for Assessing Pathogenicity of <em>Ustilago maydis</em> on Maize and Teosinte Lines

Abstract: Maize is a major cereal crop worldwide. However, susceptibility to biotrophic pathogens is the primary constraint to increasing productivity. U. maydis is a biotrophic fungal pathogen and the causal agent of corn smut on maize. This disease is responsible for significant yield losses of approximately $1.0 billion annually in the U.S.1 Several methods including crop rotation, fungicide application and seed treatments are currently used to control corn smut 2 . However, host resistance is the only practical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Ustilago maydis , also known as Ustilago zeae and Ustilago zeae mays , is a biotrophic fungus that causes Corn Smut (Common Smut, Boil Smut) [58] (Table 1). It can enter the plant at various sites, including silks which results in large fungal growths (galls) on the ear [58,59,60].…”
Section: Globally Important Pathogens That Infect Maize Silks and mentioning
confidence: 99%
See 1 more Smart Citation
“…Ustilago maydis , also known as Ustilago zeae and Ustilago zeae mays , is a biotrophic fungus that causes Corn Smut (Common Smut, Boil Smut) [58] (Table 1). It can enter the plant at various sites, including silks which results in large fungal growths (galls) on the ear [58,59,60].…”
Section: Globally Important Pathogens That Infect Maize Silks and mentioning
confidence: 99%
“…Ustilago maydis , also known as Ustilago zeae and Ustilago zeae mays , is a biotrophic fungus that causes Corn Smut (Common Smut, Boil Smut) [58] (Table 1). It can enter the plant at various sites, including silks which results in large fungal growths (galls) on the ear [58,59,60]. However, infection by U. maydis is not exclusively viewed in a negative light by local peoples; Huitlacoche or “maize mushrooms” are ear galls caused by Corn Smut which are eaten as a delicacy in Mexico, Central America, and the United States [59,60].…”
Section: Globally Important Pathogens That Infect Maize Silks and mentioning
confidence: 99%
“…Using these approaches Lennon et al was able to identify the teosinte-derived GLS resistance QTL located in bin 4.07. Teosinte was also reported to manifest resistance to corn smut disease (Chavan and Smith, 2014 ). Using genomic in situ hybridization technology, Wei et al ( 2001 ) identified the chromosomal locations of the Z. diploperennis- derived segments in maize × Z. diploperennis crosses that carried loci resistant to fungal diseases including northern corn leaf blight, southern corn leaf blight, and corn leaf spot diseases.…”
Section: Maizementioning
confidence: 99%
“…maydis is a basidiomycete that belongs to the Ustilagenaceae family, which is composed of fungi that are related to the infection of several types of crops. It is studied because of its biotechnological potential for producing value added compounds such as organic acids, enzymes, lipids, and biosurfactants, among others, with applications in the pharmaceutical, cosmetic, and food industries (Chavan and Smith, 2014;Paulino et al, 2017). As a biotrophic organism, U. maydis requires the plant to continue its growth, transiting between two forms during its cell cycle, a yeast-like saprophytic phase and a filamentous phytopathogenic phase (Chavan and Smith, 2014).…”
Section: Introductionmentioning
confidence: 99%